O uso da astronomia com auxílio de tecnologias e dinâmicas para o ensino da física - Vasconcelos, Thyago Teixeira (2018)
This work was developed with the purpose of supporting the physics teacher in his teaching practice, targeting high school students from public schools or science students from the ninth year of elementary school. The educational product is based on five topics (Scientific Measurements, Study of Motion, Force, Temperature and Heat, Light and Radiation) that allow the use of astronomy as an interdisciplinary and motivational science for the teaching of physics. Teaching tools include play activities such as wordplay and crossword puzzles, as well as simulations and animations with the aid of computers from the computer rooms and digital whiteboard for interactive presentations with the students. The materials in annexes are constituted by scripts of practices in PhET (Physics Education Technology) among other animations, a series of word-searchers and crosswords. The whole script was used as a teaching-learning tool with the purpose of developing capacity for concentration and memorization, serving as a basis for the understanding of concepts motivating the teaching of physics in basic education focusing on Astronomy.